Creep deformation and rupture behaviour of boron-added P91 Steel. Issue 5 (24th March 2021) - Sakthivel, T.; Sasikala, G.; Syamala Rao, P.; Parameswaran, P.; Laha, K.
Abstract : Creep deformation and rupture behaviour of P91 and boron-added P91BN steels were investigated over the stress range of 100–350 MPa at 823, 873 and 923 K. The time spent in each creep regime was significantly higher in P91BN steel as compared to P91 steel. The reduction in the minimum creep rate in P91BN steel about one to two orders of magnitude was observed than that in the P91 steel. An addition of boron (0.006 wt-%) with controlled nitrogen content (0.011 wt-%) in P91BN led to better creep rupture strength than the P91 steel. Using the Larson–Miller parametric method, creep rupture strength evaluated at 873 K for 10 5 h life was about 33% enhancement in the case of P91BN steel than P91 steel.